PEMBELAJARAN DI MADRASAH IBTIDAIYAH DAPAT MENJADI SALAH SATU BASIS PEMBENTUKAN MANUSIA BERKARAKTER - Much Rofiq (As-Sibyan, 2020)
Recently, our society is covered with the feeling of anxious and restless without the tip of the base. It is related to the next generation (their children) especially about the thing related to their characters. The developments of science and technology that run so fast and tend to be uncontrollable have accelerated the development of children’s cognitive aspect, too. It made the affective aspect has been far left behind. The fact that nowadays many mothers who are working outside the house minimizes the opportunity to communicate with their children. That makes their children lack of affection, lack of guidance, and the warmth of their existence. This kind of condition encourages the children to seek their inner fulfillment by using provided social media without any guidance from their parents. In essence, parents are the first and the primary educators for their own children. It is said that parents are the first educator for their children because the children come from families. From the beginning, parents should be responsible for fostering children’s character. If parents are rarely at home, it will never happen. The children will grow without the supervision and guidance from their parents. Furthermore, it is said that parents as the primary educators. It means that parents are the main painter of children’s character. Those two things I have mentioned above are the main characteristics of education in a family.